2022
DOI: 10.5194/nhess-22-3487-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ignition probability for human- and lightning-caused wildfires in Victoria, Australia

Abstract: Abstract. Wildfires pose a significant risk to people and property, which is expected to grow with urban expansion into fire-prone landscapes and climate change causing increases in fire extent, severity and frequency. Identifying spatial patterns associated with wildfire activity is important for assessing the potential impacts of wildfires on human life, property and other values. Here, we model the probability of fire ignitions in vegetation across Victoria, Australia, to determine the key drivers of human-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…When LFMC is dry, the probability of a fire given a lightning strike is 2.25%, compared to 1.27% when LFMC is wet (Figure 4d). These low probabilities of lightning ignitions are consistent with previous research (Abatzoglou et al, 2016;Dorph et al, 2022;Nampak et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When LFMC is dry, the probability of a fire given a lightning strike is 2.25%, compared to 1.27% when LFMC is wet (Figure 4d). These low probabilities of lightning ignitions are consistent with previous research (Abatzoglou et al, 2016;Dorph et al, 2022;Nampak et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Each lightning pair consists of a dry‐LFMC strike and a wet‐LFMC strike, with land cover being identical and all other wildfire‐related properties being as similar as possible. As covariates, we consider latitude and longitude, above‐ground biomass (AGB) and dead biomass to control for fuel availability (Hessilt, 2022; Safford et al., 2022), wind speed on the lightning day (Goss et al., 2020), cumulative precipitation 12 months before the lightning day, average vapor pressure deficit (VPD) over the 4 months before the lightning day to control for soil moisture (Dadap et al., 2019), and litter moisture effects (Dorph et al., 2022) (Table S1 in Supporting Information ). We use lagged aggregates for precipitation and VPD rather than instantaneous values because soil moisture and litter moisture have memory (McColl et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bates et al [138] used the Bayesian network as a framework to assess climate variability in lightning-induced wildfires, and unlike the lightning ignitions, the climate modes were allied to the fire weather conditions. Dorph et al's [139] study in Victoria, Australia, also indicated that lightning-caused wildfires are steered by weather conditions. Clarke et al [140] developed fire models to investigate lightning-induced wildfires in southeastern Australia, specifically Victoria, South Australia, and Tasmania.…”
Section: Asia and Australiamentioning
confidence: 98%
“…There are still important knowledge gaps about LIWs. Although LIWs are often studied in boreal and temperate ecosystems of North America (e.g., Abatzoglou et al, 2016;Veraverbeke et al, 2017), in other regions, such as Europe and Australia, LIWs receive less attention because of their lower occurrence or burned area in comparison with human-caused fires (Conedera et al, 2006;Ganteaume et al, 2013;Ganteaume and Syphard, 2018;Dorph et al, 2022). Similarly, LIWs are less studied in South America, Asia and Africa (e.g., Manry and Knight, 1986;Kharyutkina et al, 2022;Menezes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%